The Remasculinization of Korean Cinema - Kim, Kyung Hyun, 1969- (Book collections on Project MUSE., 2004)
Argues that although the last two decades of Korean history were a period of progress in political democratization, the country refused to part from a "masculine point of view" which is also mirrored in Korean cinema.